Synthesis and characterization of some novel diaryl urea derivatives bearing quinoxalindione moiety - Sedighe Sadeghian-Rizi; Ghadamali Khodarahmi; Amirhossein Sakhteman; Ali Jahanian-Najafabadi; Mahboubeh Rostami; Mahmoud Mirzaei; Farshid Hassanzadeh (Wolters Kluwer Medknow Publications, 2018)
Diaryl urea derivatives have exhibited a broad spectrum of biochemical effects and pharmaceutical applications. Several diaryl urea derivatives such as sorafenib, regorafenib, linifanib, and tivozanib and lenvatinib are in clinical trial or clinical use. Therefore, development of small molecules within the diaryl urea scaffold with the ability of binding to variety of enzymes and receptors in the biological system are an interesting topic for researchers. Sorafenib as a diaryl urea derivative is a well-known anticancer agent. Corresponding to available information about biological activities of quinoxaline moieties, based on sorafenib scaffold, several structures were designed by replacement of pyridyl carboxamide group of sorafenib with quinoxalindione moiety. A total of 14 novel compounds in 7 synthetic steps were synthesized. Briefly, the amino group of p-aminophenol was first protected followed by O-arylation of 4-acetamidophenol with 5-chloro-2-nitroaniline to provide 5-(4-acetamidophenoxy)-2-nitroaniline. Reduction of the nitro group of 5-(4-acetamidophenoxy)-2-nitroaniline and cyclization of diamine N-(4-(3,4-diaminophenoxy) phenyl) acetamides with oxalic acid afforded compound N-(4-((2,3-dioxo-1,2,3,4-tetrahydroquinoxalin-6-yl)oxy)phenyl) acetamides which on deacetylation gave compounds 6-(4-aminophenoxy) quinoxaline-2,3 (1H, 4H)-diones. Then resultant compounds, 6-(4-aminophenoxy) quinoxaline-2,3 (1H, 4H)-diones were reacted by appropriate isocyanates/ carbamates to give the target compounds 1-(4-((2,3-dioxo-1,2,3,4-tetrahydroquinoxalin-6-yl)oxy)phenyl)-3-phenylureas. The structures of compounds confirmed by proton nuclear magnetic resonance (1H NMR), mass spectrum and Fourier transform infrared (FT-IR).